Correlation Between Mehlich-3 and Ammonium Acetate Extractable Potassium in Kansas Soils - B. Rutter; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2019)
The K-State Research and Extension Soil Testing Laboratory has been using Mehlich-3 soil test procedures for phosphorus (P) extraction, and ammonium acetate extraction for potassium (K). Previous research in other states has shown a strong correlation between these two tests for K, but data correlating the two in Kansas soils have been limited. A study was performed on soils from across the state to investigate the relationship between these two methods. A strong positive correlation was observed (r = 0.99) across the wide range of soil types, pH, and fertility conditions represented in the sample set. Linear regression suggests a near 1:1 relationship and strong fit between Mehlich-3 and ammonium acetate extractable K (slope = 0.97, R2= 0.98). Based on these results the Mehlich-3 procedure for soil K analysis is a suitable for Kansas soils.
Keywords: potassium; Mehlich-3; ammonium Acetate; correlation